In silico modeling of N294S mutation effect on the interaction of influenza virus N8 neuraminidase with zanamivir - E. A. Rukhlova; G. S. Onkhonova; M. N. Kosenko; I. M. Susloparov; I. A. Sobolev; A. B. Ryzhikov (Юг России: экология, развитие)
The aim of the study is an in silico modeling of avian influenza A/H5N8 virus neuraminidase and zanamivir interaction using homology modeling and molecular docking. A/chicken/Tatarstan/88/2017 (wild type) and A/chicken/Tatarstan/112/2017 (N294S mutation) influenza virus strains with zanamivir complexes were considered. The structures of two avian influenza virus A/H5N8 neuraminidase complexes with zanamivir were obtained and analysed.Homology modeling and molecular docking provides information about neuraminidase and inhibitors affinity. The data obtained can be used for further investigation to determine the structures and elucidate possible mechanisms of neuraminidase resistance.